2019
DOI: 10.1080/19475683.2019.1575906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of landslide susceptibility in a hill city of Sikkim Himalaya with the perspective of hybrid modelling techniques

Abstract: Landslides are common and frequent occurring phenomenon in hilly terrain during monsoon season. The primary objectives of the research work are to carry out a comprehensive analysis by quantifying the landslide susceptibility using an integrated approach of random forest (RF) with the probabilistic likelihood ratio (RF-PLR), fuzzy logic (FL) and index of entropy (IOE) in Gangtok city of Sikkim state, India. Landslide inventories are prepared based on LISS-IV (MX) satellite imagery, Google Earth and reported da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The rest of the slope directions are less susceptible to the landslides. Kaur et al [29] studied landslide at Sikkim which is one of the states of India and neighbour to Bhutan and it is also a part of the Himalayan region. Kaur et al [29] observed that the south, southeast, and southwest with a higher value of (Pij).…”
Section: Results and Discussion 1) The Spatial Relationship Between Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the slope directions are less susceptible to the landslides. Kaur et al [29] studied landslide at Sikkim which is one of the states of India and neighbour to Bhutan and it is also a part of the Himalayan region. Kaur et al [29] observed that the south, southeast, and southwest with a higher value of (Pij).…”
Section: Results and Discussion 1) The Spatial Relationship Between Tmentioning
confidence: 99%
“…Kaur et al [29] studied landslide at Sikkim which is one of the states of India and neighbour to Bhutan and it is also a part of the Himalayan region. Kaur et al [29] observed that the south, southeast, and southwest with a higher value of (Pij). This may be due blockage of wind that comes from the south (Indian Ocean) by the giant Himalayan mountain.…”
Section: Results and Discussion 1) The Spatial Relationship Between Tmentioning
confidence: 99%
“…Elevation, slope, aspect, profile curvature, Topographical Roughness Index (TRI), Topographical Wetness Index (TWI), and Stream Power Index (SPI) extracted from the Digital Surface Model (DSM) are provided by the ALOS Global Surface Model. Lineaments [23] include faults, ridgelines, fissures, or boundaries between strata on the Earth's surface, with different lengths and orientations. To extract the lineaments in the study area, the DSM is used to obtain 0 • , 45 The raster data for lithology and landform are obtained from A New Map of Global Ecological Land Units [24] and The New Global Lithological Map Database [25].…”
Section: Data Preparationmentioning
confidence: 99%
“…Approximately CHF 15 million are spent each year on landslide protective measures in Switzerland (Dorren et al, 2009). To mitigate this risk, regional landslide hazard mapping and modelling provide an important basis for indicating potential hazard areas (Dahl et al, 2010;Kaur et al, 2019;Shano et al, 2020;Di Napoli et al, 2021). In Switzerland, nationalscale shallow landslide modelling was carried out at within the SilvaProtect-CH project (Dorren and Schwarz, 2016).…”
Section: Introductionmentioning
confidence: 99%